Evaluation of Methanotroph (Methylococcus capsulatus, Bath) Bacteria Meal (FeedKind®) as an Alternative Protein Source for Juvenile Black Sea Bream, Acanthopagrus schlegelii - Xu, Bingying; Liu, Yuechong; Chen, Kai; Wang, Lei; Sagada, Gladstone; Tegomo, Arnaud Fabrice; Yang, Yifei; Sun, Yuxiao; Zheng, Lu; Ullah, Sami; Shao, Qingjun (Frontiers in Marine Science, 2021)
Single cell proteins are attracting growing attention as viable alternatives for fishmeal (FM) in aquatic feed. Methanotroph (Methylococcus capsulatus, Bath) bacteria meal FeedKind® (FK) is a type of single cell protein with high protein content (75.14%) and desirable amino acids profile, produced by Methylococcus capsulatus (Bath) living on methane consumption. The present study evaluated the potential of replacing FM with FK in the diet of black sea bream (Acanthopagrus schlegelii). Five iso‐energetic and iso‐nitrogenous diets were designed with FK replacing 0%, 4.13%, 8.27%, 16.53%, and 24.80% FM protein in the basal diet (40% FM content), respectively. All the diets were fed to three replicates of fish (initial weight 6.56 ± 0.02 g) for 70 days. After the feeding trial, replacing dietary 8.27% FM protein with FK significantly improved the weight gain and specific growth rate of fish (P < 0.05), while other groups showed no significant difference in the growth performance (P > 0.05). The fish fed diets with 8.27% and 16.53% replacement levels exhibited significantly increased feeding rate. The 8.27% FK diet significantly increased the whole-body and muscle crude protein contents, apparent digestibility of crude lipid, foregut and midgut amylase activities. The microvillus density in the midgut of fish fed the 24.80% FK diet significantly increased. The diet with 8.27% FK increased the serum triglyceride content of the fish, while the 24.80% FK diet reduced the serum triglyceride, total cholesterol, and low-density lipoprotein cholesterol contents of fish. In conclusion, the results indicated that replacing dietary FM protein with up to 24.80% FK had no adverse effects on the growth of black sea bream, whilst replacing 8.27% FM protein with FK enhanced its growth performance and feed utilization.